The Influence of Information Technology and the Development of Soft Skills of the Millennial Generation in Facing the World of Work in the Final Semester Students of the Management Study Program Faculty of Economics and Business, Pancasakti University - Susilawati, Agnes Dwita; Hapsari, Ira Maya; Subroto, Setyowati; Awaliyah, Putri Aulia Nisfi; Prihadi, Deddy; Irawan, Bei Harira (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The current era of globalization has been increasing and has strong competitiveness between companies encouraging each university to improve the quality and readiness of students to enter the world of work. Facing increasingly fierce job competition, the Faculty of Economics and Business, Pancasakti University Tegal is trying its best to create graduates who are professional, competent, and highly competitive globally. The Management Study Program strives to produce students who are ready to work, creative, innovative and have a high entrepreneurial spirit. This study aims to investigate the impact of information technology and soft skill development on the millennial generation's preparedness for the workforce. The population consists of 303 undergraduate students enrolled in the Faculty of Economics and Business class 2021-2022 at Pancasakti Tegal University, with a research sample of 172 respondents. Purposive sampling was employed to select participants, and data analysis was conducted using Multiple Linear Regression analysis with SPSS data processing tool version 23 for windows. The analysis revealed a significant positive relationship between Information Technology (X1) and readiness for the workforce (Y), as evidenced by a t-count of 6.077 exceeding the critical t-value of 1.974 (p < 0.001). This supports the acceptance of H1. The analysis revealed no significant relationship between Soft Skills (X2) and readiness for the workforce (Y), as evidenced by a calculated value of 0.234, which is less than the critical t-value of 1.974 (p = 0.219). This leads to the rejection of H2. The influence of Information Technology and Soft skills has an influence on facing the world of work was determined to be 52.0%, while the remaining 48.0% of the variance can be attributed to other factors that were not included within the scope of this study such as hard skills, work motivation, communication and so on. This research can also be used as a reference for students in developing further research